Influence of different methods of breaking seeds dormancy of Ambrosia artemisiifolia, Abutilon theophrasti and Xanthium strumarium on emergence in field conditions - Krstić, Jovana (Acta herbologica, 2021)
Seeds dormancy is an important trait that contributes to their survival rate, helps to avoid the effects of herbicides, and protects against adverse environmental conditions. In order to determine which methods are effective in breaking seeds dormancy of invasive weed species (Ambrosia artemisiifolia, Abutilon theophrasti, Xanthium strumarium), an experiment was set up in 2019 according to a randomized block design with three replication in the experimental field of the Institute of Field and Vegetable Crops (Novi Sad). The collected seeds of one population of A. artemisiifolia and A. threophrasti, until testing, were cleaned and stored in cold storage at 4 ℃, while X. strumarium was stored at room temperature. Seed propagation was done in a herbology laboratory using nine different methods of breaking seeds dormancy. The seeds were exposed to different conditions of temperature, light and humidity in a certain period of time (24h or 48h). The dynamics of weed emergence were monitored daily for a period of 31 days and expressed cumulatively in percentages. Based on the obtained results, the highest percentage of sprouted plants was determined in treatments where the seeds were propagated under the light in water. An appropriate method of propagation can influence the breaking seeds dormancy and emergence in field conditions, which can have practical significance in the research of competitive relations between crops and tested weed species.
Keywords: breaking seeds dormancy, Ambrosia artemisiifolia, Abutilon theophrasti, Xanthium strumarium